2019
DOI: 10.3389/fmars.2019.00735
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Meiofauna Assemblages and Their Relationship With Environmental Factors of Deep Sea Adjacent to the Yap Trench, Western Pacific Ocean

Abstract: Sediment samples were collected from 23 sites near the Yap Trench in the Western Pacific Ocean with a depth range of 2896-7837 m. The assemblage composition, spatial distribution, and relationship with environmental variables of meiofauna were studied. A total of 17 meiofaunal taxa were identified, including free-living marine nematodes, benthic copepods, nauplii, ostracods, halacarids, kinorhynchs, cumaceans, turbellarians, cladocerans, polychaetes, oligochaetes, isopods, tanaidaceans, amphipods, tardigrades,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The increase in the abundance of meiobenthic nematodes (which was maximum on the bottom of the deepest basins of the Kuril-Kamchatka Trench) with depth is probably also associated with the increased organic matter content of bottom sediments of the trench (Schmidt et al, 2019). The increase in the abundance of meiofauna with increasing depth have been repeatedly reported in other studies on eutrophic trenches (George and Higgins, 1979;Shirayama and Kojima, 1994;Danovaro et al, 2002;Leduc et al, 2016;Schmidt et al, 2018;Wang et al, 2019). However, the abundance of large macrobenthic nematodes, unlike meiobenthic ones, on the Kuril-Kamchatka Trench floor was minimum and generally lower than in the abyssal zone of the eutrophic regions of the North Pacific.…”
Section: The Hadal Zone Of the Kuril-kamchatka Trenchsupporting
confidence: 70%
See 2 more Smart Citations
“…The increase in the abundance of meiobenthic nematodes (which was maximum on the bottom of the deepest basins of the Kuril-Kamchatka Trench) with depth is probably also associated with the increased organic matter content of bottom sediments of the trench (Schmidt et al, 2019). The increase in the abundance of meiofauna with increasing depth have been repeatedly reported in other studies on eutrophic trenches (George and Higgins, 1979;Shirayama and Kojima, 1994;Danovaro et al, 2002;Leduc et al, 2016;Schmidt et al, 2018;Wang et al, 2019). However, the abundance of large macrobenthic nematodes, unlike meiobenthic ones, on the Kuril-Kamchatka Trench floor was minimum and generally lower than in the abyssal zone of the eutrophic regions of the North Pacific.…”
Section: The Hadal Zone Of the Kuril-kamchatka Trenchsupporting
confidence: 70%
“…However, the abundance of large macrobenthic nematodes, unlike meiobenthic ones, on the Kuril-Kamchatka Trench floor was minimum and generally lower than in the abyssal zone of the eutrophic regions of the North Pacific. The phenomenon of meiofaunal miniaturization was reported earlier for both oligotrophic and eutrophic deep-sea waters of the world's oceans (Shirayama, 1984;Schewe and Soltwedel, 1999;Danovaro et al, 2002;Wang et al, 2019). After studying the meiofauna of the eutrophic Atacama Trench, Danovaro et al (2002) showed that meiofaunal miniaturization cannot be related to the reduced food availability or to oligotrophic conditions, as previously suggested by Schewe and Soltwedel (1999).…”
Section: The Hadal Zone Of the Kuril-kamchatka Trenchsupporting
confidence: 69%
See 1 more Smart Citation
“…After generally 30 days, the experiment was conducted adding 4% buffered formalin solution in the experimental plots. Using the Ludox™ centrifugation technique and sieves (40 μm -1 mm), the meiobenthic nematodes were extracted from the sediments and stained for 48 h with Rose Bengal [22]. Afterward, meiofaunal taxa were identified and counted under a stereomicroscope (50×, Wild Heerbrugg M5A Model), and a maximum of 100 nematodes/replicates were randomly collected.…”
Section: Sediment Contamination and Nematodes Studymentioning
confidence: 99%
“…ISSN: 1659-455X • e-ISSN: 1659-407X DOI: http://dx.doi.org/10.15359/revmar.12-2.5 the energy produced by microalgae and bacteria to benthic consumers of higher trophic levels (Moncreiff & Sullivan, 2001;Ansari et al 2012). Meiobenthos modify the physical, chemical, and biological properties of sediments, participating in sediment stabilization, biogeochemical cycles, and waste removal (Wang et al 2019). Additionally, it has been widely used for monitoring environmental quality due to its fast response to changes in the environment, species richness, and short life cycles with 3 to 5 generations per year (Giere, 2009;Ansari et al 2012;Kitahashi et al 2018).…”
Section: Introductionmentioning
confidence: 99%